2017
DOI: 10.17219/acem/68739
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin: Intracellular mechanisms of action and its role in the pathogenesis of skeletal and vascular disorders

Abstract: Sclerostin is a glycoprotein involved in the regulation of bone metabolism, exclusively secreted by osteocytes. It affects the activity of bone morphogenetic proteins (BMPs) and is an inhibitor of the Wnt/β-catenin metabolic pathway in bone cells. Osteocytes reduce the release of sclerostin in response to mechanical stimuli acting on bone, and thus promote the activation of osteogenic pathway Wnt/β-catenin in osteoblasts. This signaling pathway plays a key role in osteogenesis and bone turnover. Loss of sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…Of note, recently it has been shown that osteocytes can be considered as a source of anabolic factors such as Wnt1, able to speed up osteoblastogenesis by triggering Wnt signaling in osteoblasts (Joeng et al, 2017). It is also well known that osteocytes are a source of osteoprotegerin, the potent inhibitor of RANKL, that mediates the inhibition of bone resorption, but conversely they are also the producers of Sclerostin, the most important anti-anabolic regulator of bone formation by osteoblasts (Pietrzyk et al, 2017;Tatsumi et al, 2007;Weinstein et al, 2011;Xiong et al, 2014). During the last decade, in order to regulate the process of bone remodeling in osteoporotic patients, PTH (1-34), also known as TPTD, has been used as an anabolic drug (Bellido et al, 2013;Giannotti et al, 2013;Riek and Towler, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, recently it has been shown that osteocytes can be considered as a source of anabolic factors such as Wnt1, able to speed up osteoblastogenesis by triggering Wnt signaling in osteoblasts (Joeng et al, 2017). It is also well known that osteocytes are a source of osteoprotegerin, the potent inhibitor of RANKL, that mediates the inhibition of bone resorption, but conversely they are also the producers of Sclerostin, the most important anti-anabolic regulator of bone formation by osteoblasts (Pietrzyk et al, 2017;Tatsumi et al, 2007;Weinstein et al, 2011;Xiong et al, 2014). During the last decade, in order to regulate the process of bone remodeling in osteoporotic patients, PTH (1-34), also known as TPTD, has been used as an anabolic drug (Bellido et al, 2013;Giannotti et al, 2013;Riek and Towler, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of Runx2 expression by SPRY2 was documented also in other system. 14 Regarding osteocytes identified by their typical marker, sclerostin, 16 Sost mRNA was strongly up-regulated in Spry2-/-tibias. Immunolabelling showed only a slight nonsignificant increase of SOST-positive osteocytes in Spry2-/-tibias.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, very recent research shows that SOST-Fc vaccination might be a therapeutic approach for preventing osteoporosis [ 42 ]. So far, it has not been established how anti-sclerostin antibodies affect vascular calcifications [ 43 ]. These studies will provide first clinical information’s how sclerostin blocking antibodies might affect vascular calcification or vascular stiffness.…”
Section: Methodsmentioning
confidence: 99%